1984
DOI: 10.1007/bf00275655
|View full text |Cite
|
Sign up to set email alerts
|

Congenital rubella syndrome as a model for Type 1 (insulin-dependent) diabetes mellitus: increased prevalence of islet cell surface antibodies

Abstract: An increased prevalence of Type 1 (insulin-dependent) diabetes has been reported in patients with congenital rubella. Rubella virus multiplies in the pancreas, and we have hypothesized that studies of children with congenital rubella would be of great importance in following the development of Type 1 diabetes in a defined, susceptible population. Two hundred and forty-one children with congenital rubella (mean age 17.4 +/- 0.3 years; 65% black and hispanic) have been evaluated, 30 of whom already have diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(43 citation statements)
references
References 12 publications
1
41
0
1
Order By: Relevance
“…Interestingly, several other endocrine diseases (25)(26)(27), thought to be autoimmune, can also develop following congenital rubella infection. Autoantibodies to tissue-specific antigens have been identified in the sera of patients with rubella-associated endocrine disease, suggesting their autoimmune pathogenesis (28,29).…”
Section: Viruses As Triggers Of Autoimmunitymentioning
confidence: 99%
“…Interestingly, several other endocrine diseases (25)(26)(27), thought to be autoimmune, can also develop following congenital rubella infection. Autoantibodies to tissue-specific antigens have been identified in the sera of patients with rubella-associated endocrine disease, suggesting their autoimmune pathogenesis (28,29).…”
Section: Viruses As Triggers Of Autoimmunitymentioning
confidence: 99%
“…Recently, we reported that CVB4 JVB (a laboratory reference strain) and CVB4 E2 persistently infect human TEC in vitro, and we hypothesized that this persistence could interfere with thymus function and contribute to the development of autoimmunity (5). Congenital rubella syndrome provides an example of in utero acquired infection causing type 1 diabetes (14); therefore, it has been suggested that fetal viral infections may be causally related to type 1 diabetes (10). Otonkoski et al detected postnatally several types of diabetes-associated autoantibodies in an infant infected in utero by an enterovirus, which suggests that enterovirus infections in utero may induce ␤-cell autoimmunity (36).…”
mentioning
confidence: 99%
“…Type I diabetes that is CRS-associated has been used as a model to study the viral influences in the pathogenesis of the disease [7,30]. The present study suggests that the positive frequencies responding to cross-reactive determinents beta-cell epitopes B4, GAD65(274±286) and B10, GAD67(212±226), and RV peptides V3, RVE1(157±176) of PBMC from patients of CRS-associated Type I diabetes seem to be higher than those of PBMC from patients of CRS without Type I diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The best-documented information linking a preceding viral infection in humans with the subsequent onset of diabetes has come from studies of children and young adults who were infected with RV during intra-uterine development and subsequently diagnosed as having congenital rubella syndrome (CRS) [1,4,5]. The incidence of insulin-dependent diabetes in CRS patients has been estimated to be 10±12 % whereas up to 40 % of CRS patients show impaired glucose tolerance [3,6,7]. Results of studies in mice and humans with Type I diabetes suggest that beta-cell destruction could occur directly as a result of viral replication or indirectly due to viral bystander damage or viral induction of autoimmune cell damage [1,4,8].…”
mentioning
confidence: 99%
See 1 more Smart Citation